A Versatile Route to Red-Emitting Carbopyronine Dyes for Optical Microscopy and Nanoscopy - Kolmakov, K; Belov, V; Wurm, C; Harke, B; Leutenegger, M; Eggeling, C; Hell, S (2010)
Biological microscopy favors photostable fluorescent markers with large fluorescence quantum yields, low dark triplet state population, good biocompatibility and absorption and emission maxima in the near-infrared, where cellular autofluorescence is minimized. In the present study, carbopyronines absorbing around 640 nm and emitting at around 660 nm, with a low intersystem crossing rate (kisc ≈ 0.5×106 s-1) and excellent properties for cellular imaging were synthesized. A general synthetic route to carbopyronines with functional groups variable in the final steps of the synthesis or in the resulting fluorescent dye is presented. Possessing two 2-me-thoxyethyl groups, the parent dye is soluble in water and most organic solvents. Demethylation of the dye or its precursors is straightforward, clean, and furnishes compounds with one or two 2-hydroxyethyl groups, which can be used for further transformations. Modifications in the linker-containing carboxy group are also possible. A multistep synthesis of the dye starting from a simple precursor and utilizing a single temporary protective group is described. The presented approach may be further applied to the design of caged carbopyronines. © 2010 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.